2018
DOI: 10.3390/cancers10110428
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis Comparing Liver Resection with the Rf-Based Device Habib™-4X with the Clamp-Crush Technique

Abstract: Liver cancer is the sixth most common cancer and third most common cause of cancer-related mortality. Presently, indications for liver resections for liver cancers are widening, but the response is varied owing to the multitude of factors including excess intraoperative bleeding, increased blood transfusion requirement, post-hepatectomy liver failure and morbidity. The advent of the radiofrequency energy-based bipolar device Habib™-4X has made bloodless hepatic resection possible. The radiofrequency-generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 89 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…20,21 Interestingly, it has also been reported that liver transections using radiofrequency energy may improve the survival rate in cases of hepatocellular carcinoma by reducing blood loss and transfusion rate. 22,23 A number of randomized controlled trials (RCTs) have been reported on the methods of liver parenchymal transection using various devices. [1][2][3][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Although the results varied, none of the devices used for transection showed significant advantages over the classical crushing clamp method.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Interestingly, it has also been reported that liver transections using radiofrequency energy may improve the survival rate in cases of hepatocellular carcinoma by reducing blood loss and transfusion rate. 22,23 A number of randomized controlled trials (RCTs) have been reported on the methods of liver parenchymal transection using various devices. [1][2][3][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Although the results varied, none of the devices used for transection showed significant advantages over the classical crushing clamp method.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative bleeding from the hepatic vein is a major issue for surgeons during anatomical hepatectomy when the vein is longitudinally exposed within the section being transected . Thick Glissonean branches rarely appear in the liver transection plane during hemi‐hepatectomy, and bleeds from such branches are usually small.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative bleeding is a major issue for hepatic surgeons not only because a large volume of intraoperative blood loss is a major cause of postoperative complications, but also because blood transfusions compromise oncological outcomes . During hemi‐hepatectomy, thick Glissonean vessels rarely appear at the site of parenchymal transection, but bleeding from these vessels is controllable using hepatic pedicle occlusion .…”
Section: Introductionmentioning
confidence: 99%
“…According to meta-analysis performed by Ding et al, increased density of tumour infiltrating lymphocytes (TILs) have been significantly associated with improved survival [78]. Additionally, studies have outlined positive immunomodulatory change following the application of RF in terms of Tregs, CD8+ T-cells, TGF-β, IFNγ, IL-10, IL-17, respectively [79][80][81][82].…”
Section: Hcc Tumour Microenvironment Immunomodulation Through Combinementioning
confidence: 99%
“…immunomodulatory change following the application of RF in terms of Tregs, CD8+ T-cells, TGF-β, IFNγ, IL-10, IL-17, respectively [79][80][81][82].…”
Section: Hcc Tumour Microenvironment Immunomodulation Through Combinementioning
confidence: 99%